2016
DOI: 10.1111/ped.12845
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric extended spectrum β‐lactamase infection: Community‐acquired infection and treatment options

Abstract: The increase in infection caused by ESBL-producing Enterobacteriaceae limits the availability of effective antibiotics. Given that carbapenems are necessary for treating serious infections, amikacin, cefepime, and piperacillin/tazobactam are possible options for consolidative therapy or for non-serious infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…They also found the vast majority of ESBL-producing isolates were susceptible to amikacin but noted that poor tissue penetration and potential nephrotoxicity limited the use of amikacin and other aminoglycosides outside of urinary tract infections. 40 Another potential treatment option is piperacillin/tazobactam, but we found substantial non-susceptibility (> 25%) to this combination among ESBL-producing K. pneumoniae isolates, similar to Sethaphanich, 39 who found only 62.6% of K. pneumoniae isolates were susceptible to piperacillin/tazobactam. This makes it a poor choice for empiric treatment.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…They also found the vast majority of ESBL-producing isolates were susceptible to amikacin but noted that poor tissue penetration and potential nephrotoxicity limited the use of amikacin and other aminoglycosides outside of urinary tract infections. 40 Another potential treatment option is piperacillin/tazobactam, but we found substantial non-susceptibility (> 25%) to this combination among ESBL-producing K. pneumoniae isolates, similar to Sethaphanich, 39 who found only 62.6% of K. pneumoniae isolates were susceptible to piperacillin/tazobactam. This makes it a poor choice for empiric treatment.…”
Section: Discussionsupporting
confidence: 70%
“…We found a high prevalence of resistance to third-generation cephalosporins among ESBL-producing E. coli and K. pneumoniae , which is consistent with previous reports from Thailand. 38 A 2016 report 39 examined treatment options for children (0–15 years) with E. coli and K. pneumonia e infections visiting a tertiary care center in Bangkok. They also found the vast majority of ESBL-producing isolates were susceptible to amikacin but noted that poor tissue penetration and potential nephrotoxicity limited the use of amikacin and other aminoglycosides outside of urinary tract infections.…”
Section: Discussionmentioning
confidence: 99%
“…pneumoniae was the most frequent (44.8%) causes of infections in children under 5 years of age. However, comparatively low prevalence of ESBL (40%) was reported in paediatric infection in Thailand [19]. Therefore, children infected with Enterobacteriaceae species need a great emphasis prior to selection of antimicrobial therapy.…”
Section: Discussionmentioning
confidence: 99%
“… 12 A recent study of isolates from pediatric participants found that apart from cephalosporins, ESBL-producing strains of E. coli and K. pneumoniae were less likely to be susceptible to other antibacterial agents, such as amoxicillin/clavulanic acid, quinolones, gentamicin, netilmicin, and cotrimoxazole. 20 Thus, having options that are effective against these multidrug-resistant organisms, such as ceftolozane/tazobactam, is important.…”
Section: Discussionmentioning
confidence: 99%